Tree ferns dominate secondary succession in abandoned pineapple plantations around Manu National Park, Peru - Schilling, Olivia; Tejedor, Adrian (Universidad de Málaga. Servicio de Publicaciones e Intercambio Científico, 2017)
Habitat management and restoration in buffer zones of national parks is critical for maintaining ecosystem services and biological connectivity in and around the parks’ core protected areas. Vegetation succession in abandoned plantations in buffer zones may take different paths that reach climax ecosystems in more or less time depending on the conditions of initial succession, thus enhancing or hindering biological connectivity and ecosystem services. This study documents the dominance of tree ferns in the initial stages of vegetation succession on abandoned pineapple plantations on the Andean foothills around Manu National Park, Peru, and discusses the role it may have on ecosystem restoration. Four years after abandonment, tree fern gametophytes grow under the shade of pineapple plants and melastomes. After 6-10 years of succession, the vegetation is dominated by a tree fern community composed of at least eight species, of which the most common are by far Cyathea delgadii and Cyathea microdonta. Cyathea microdonta functions as a short-lived pioneer, reaching its peak of live stem density in 6 to10 years and dying off in older plots. Cyathea delgadii, on the other hand, continues to grow and persists beyond 10 years of succession. Areas adjacent to abandoned pineapple fields have few tree ferns and higher tree species diversity, suggesting that pineapple agriculture and the resulting tree fern community may be a longer pathway to reach climax vegetation stages than other types of plantation.
Los helechos arborescentes dominan la sucesión secundaria en plantaciones de piña abandonadas alrededor del Parque Nacional del Manu, Perú
Keywords: Helechos - Perú; Manu National Park; Amazon; Peru; Tree ferns; Vegetation succession; Parque Nacional del Manu; Amazonia; Perú; Sucesión ecológica